Community Development Blocks with 20 Percent and above Scheduled Caste Population Concentration - Planning Commission (Planning Commission, Government of India, 1978)
The Planning Commission’s October 1978 report on Community Development (C.D.) Blocks with 20 percent and above Scheduled Caste (SC) population concentration presents a comprehensive policy framework under the Five Year Plan (1978–83) to advance the socio-economic upliftment of marginalized rural communities through the Integrated Rural Development Programme (IRDP). Identifying 503 out of 5,026 C.D. blocks nationwide as having significant SC population concentrations, the document provides detailed statewise demographic data, including total population figures, SC population percentages, and coverage under major developmental schemes. The report emphasizes targeted intervention in approximately 3,500 blocks, prioritizing regions with higher SC representation to ensure equitable distribution of resources and developmental benefits. States such as Uttar Pradesh, Bihar, Andhra Pradesh, Madhya Pradesh, Maharashtra, and West Bengal are analyzed extensively, with Uttar Pradesh and West Bengal showing particularly high aggregate SC population shares in selected blocks. The data reveals notable disparities in program coverage, with several high-concentration blocks lacking adequate inclusion under schemes such as SFDA, DPAP, and CAD, thereby underscoring structural gaps in outreach. By systematically cataloguing demographic and developmental indicators, the report provides a strategic planning tool for policymakers to allocate resources more effectively, enhance rural infrastructure, and strengthen poverty alleviation initiatives. Overall, the document reinforces the government’s commitment to inclusive rural growth by advocating focused, data-driven interventions designed to integrate Scheduled Caste communities into the mainstream of economic development and social progress.
Government of India Planning Commission New Delhi (October, 1978)
Keywords: Community Development Blocks; Scheduled Caste Population Concentration; Integrated Rural Development Programme; Five Year Plan 1978–83; Socio-Economic Upliftment; Statewise Demographic Analysis; Rural Poverty Alleviation; Development Scheme Coverage; Uttar Pradesh SC Demographics; West Bengal SC Demographics; Targeted Policy Intervention; Inclusive Rural Growth